(3QSGdI aj GdedGFcIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi CfTC CfhGQ adeG CTQbJ ajg ESJYed LdGjG ef cd TF Edi CHO GdMb aeKd GdcQhH GdChd NdbkG s
(3BNQgG (B:s
(3hEf de jSeY cdGefG Ef Gddg gh GdLHGQ Ph GdjCS hGdQMeI ef Cdg ZjQg JbOSg hcHQg hJhcd Ydjg hGSJSde dg ESJYdGekG JeJ QSGdI GdedGFcI hddg GdMeO hGdefg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3GdBUajI HMjOQ CHGO (B((3eLGejY (B11(9)) s
Keywords: (3GdJhMjO hGdedd hGdfMds